A practical framework of quantifying climate change-driven environmental losses (QuantiCEL) in coastal areas in developing countries. Issue 101 (November 2019) - Mehvar, Seyedabdolhossein; Dastgheib, Ali; Filatova, Tatiana; Ranasinghe, Roshanka
Highlights: A coherent three-step framework is introduced to Quantify Climate change-driven Environmental Losses (QuantiCEL) in coastal areas in developing countries. The QuantiCEL framework is applied to quantify environmental losses due to different relative sea level rise and storm induced inundation and erosion scenarios in Indonesia, Bangladesh, and Sri Lanka. Food provision and tourism are the Coastal Ecosystem Services (CES) with estimated high absolute loss values by the end of the 21 st century. Art, amenity, and tourism are the highly affected CES by the end of the 21 st century with considerable percentage of loss value compared to the present-day value. Abstract: Climate change impacts threaten the coastal environment and affect Coastal Ecosystem Services (CES) that are vital to human wellbeing. Quantifying the monetary value of climate change driven environmental losses is scarce, especially in coastal areas of developing countries that have low adaptive capacity to climate change impacts. To address this knowledge gap, we present a practical framework to Quantify Climate change driven Environmental Losses (QuantiCEL) that coherently assesses the likely physical impacts of climate change on CES, and pursues the valuation of their losses with primary data collection. The framework is applied to coastal areas in three developing countries, and may serve as a useful guide for practitioners. We quantify potential environmental losses due to relative sea level rise-induced coastal inundation in Indonesia and Bangladesh, and losses due to sea level rise and storm-induced coastline recession in Sri Lanka in the next 100 years. This study illustrates the applicability of the framework in different contexts in the data-scarce developing countries. Our findings suggest that the three case studies will experience the absolute loss value of CES by the end of the 21 st century, with food provision and tourism suffering the highest losses. Moreover, art, amenity, and tourism services are highly affected CES with respect to the percentage loss relative to the present-day value of these CES. The QuantiCEL framework and its application presented in this study could help researchers, policy makers, and coastal zone managers to get better insights into likely climate change driven environmental losses in coastal areas, contributing to the development of much needed environmental risk quantification methods, and sustainable management of coastal wetlands.